2017
DOI: 10.4209/aaqr.2017.05.0190
|View full text |Cite
|
Sign up to set email alerts
|

Surface Indices of Wind, Stability, and Turbulence at a Highly Polluted Urban Site in Santiago, Chile, and their Relationship with Nocturnal Particulate Matter Concentrations

Abstract: The local meteorological factors of the cold season nocturnal particulate matter (PM) air quality problem in the western urban area of Santiago City are documented and analyzed by means of three years of multi-level temperature and turbulence measurements performed in-situ on a 30 m meteorological tower. For the 20-23 LT period in which the highest PM concentrations commonly occur, high prevalence of low wind and low vertical turbulence conditions are found. With wind speeds less than 1 m s -1 , the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The difference between the wind speed measured at the sampling sites is based on the greater turbulence of air masses produced in the eastern part of the region where the urban receptor site is located. Previous research has shown that higher wind speeds in this area occur when cold air masses begin to descend from the Andes during the evening hours (Muñoz and Corral, 2017).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The difference between the wind speed measured at the sampling sites is based on the greater turbulence of air masses produced in the eastern part of the region where the urban receptor site is located. Previous research has shown that higher wind speeds in this area occur when cold air masses begin to descend from the Andes during the evening hours (Muñoz and Corral, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…The geographical and climatic characteristics of the SMR have been associated to a large extent with unfavorable conditions for the dispersion of air pollutants (Rutllant and Garreaud, 1995;Schmitz, 2005;Ragsdale et al, 2013;Muñoz and Corral, 2017). Approximately 85% of the SMR surface is mountainous terrain that blocks the air circulation in the lower atmospheric layers.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its topography, Santiago experiences unfavorable conditions for the dispersion of air pollutants. The geographic and meteorological factors that affect air quality in this city have been extensively described (Rutllant and Garreaud, 1995;Schmitz, 2005;Ragsdale et al 2013;Toro et al 2014;Muñoz and Corral, 2017).…”
Section: Field Testsmentioning
confidence: 99%
“…Meteorological conditions sometimes determine air pollution situations, since they may aggravate pollution episodes, such as the recirculation of air parcel trajectories studied in Los Angeles [ 15 ]. However, certain meteorological conditions may also improve air quality, with the inverse relationship between particulate matter concentrations and the ventilation factor (the product of wind speed at 10 m and the mixed-layer height estimate) observed in Santiago City, Chile, being one noticeable example [ 16 ].…”
Section: Introductionmentioning
confidence: 99%